The Influence of Cultural Heritage Tourism Development in the Regional Development of Serdang Bedagai Regency - Dicki Gerhandoko; Zulkifli Nasution; Agus Purwoko (Budapest International Research and Critics University, 2022)
The objectives of this study are (1) to analyze the tourism potential of cultural heritage buildings in Serdang Bedagai Regency, (2) to analyze the factors that influence the development of cultural heritage building tourism in Serdang Bedagai Regency, (3) to analyze the tourism development strategy of cultural heritage buildings in Serdang Bedagai Regency. Serdang Bedagai Regency. The research method used is descriptive quantitative through literature study, observation, and questionnaires. The research data analysis technique used multiple regression analysis. The results of the study show (1) Serdang Bedagai Regency has the tourism potential of cultural heritage buildings, (2) Educational factors, information, management services, physical buildings, access to locations have a positive impact on tourism development of cultural heritage buildings in Serdang Bedagai Regency, (3) Serdang Bedagai Regency has a tourism development strategy for cultural heritage buildings.